2001
DOI: 10.1007/s007050170194
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhoea virus genotype 1 can be separated into at least eleven genetic groups

Abstract: Seventy-eight bovine viral diarrhoea viruses (BVDV) recently collected in Austria, France, Hungary, Italy, Slovakia, Spain and UK were genetically typed in the 5'-untranslated (5'UTR) and autoprotease (Npro) regions of the pestivirus genome. Seventy-six of the isolates were BVDV-1 and two French isolates were of the BVDV-2 genotype. Phylogenetic analysis of the 5'UTR (245 nt), including additional BVDV-1 sequences from USA, Canada, Germany, New Zealand, Mozambique and Sweden, taken from GenBank and from our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
241
3
11

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(268 citation statements)
references
References 26 publications
10
241
3
11
Order By: Relevance
“…These were further split into subgenotypes. To date,11 Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region 1 subgenotypes of BVDV-1 (Vilcek et al 2001) and 2 subgenotypes of BVDV-2 (Flores et al 2002, Vilcek et al 2004) have been described.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…These were further split into subgenotypes. To date,11 Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus Genetic characterization of Brazilian bovine viral diarrhea virus isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region isolates by partial nucleotide sequencing of the 5'-UTR region 1 subgenotypes of BVDV-1 (Vilcek et al 2001) and 2 subgenotypes of BVDV-2 (Flores et al 2002, Vilcek et al 2004) have been described.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Twenty-three of the strains Sequences from reference strains (NADL, SD-1, Singer, Osloss, NY-1 and US890; accession numbers. NC_00146, M96751, L32875, M96687, L32879 and Z79772, respectively), previously described field isolates representing 7 of 11 described subtypes (Vilcek et al 2001) and strains from Argentina (arg), Brazil (br) and Chile (cl) were obtained from the GenBank and included for comparison. Two out of ten Chilean strains (Cl-X1 and Cl-X3) clustered within the BVDV-1a subtype, whereas all Peruvian and the remaining eight Chilean strains clustered within the BVDV-1b subtype (for detail see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BVDV-2 is widespread in the United States and Canada, where it has been associated with outbreaks of severe acute BVDV or haemorrhagic syndrome (Pellerin et al 1994), but has also been reported in South America, Asia and Europe (Flores et al 2002, Park et al 2004, Cranwell et al 2005. The two genotypes can be further subdivided, and at least eleven subtypes of BVDV-1 and two of BVDV-2 have been identified (Vilcek et al 2001, Flores et al 2002. The genetic typing of BVDV has most frequently been based on sequence comparison of partial sequences of the 5' UTR, Npro or E2 regions (Vilcek et al 2001, Becher et al 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, tem sido proposta uma subclassificação de isolados do BVDV-1 em 11 subgenótipos (Vilcek et al 2001) e do BVDV-2 em pelo menos dois subgrupos . Uma característica marcante dos Pestivirus é a existência dos biotipos citopático (CP) e não citopático (NCP), de acordo com o efeito da replicação do vírus em cultivo celular.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified